2014
DOI: 10.1007/s11910-014-0474-4
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Landscape of Pediatric Brain Tumors in the Next-Generation Sequencing Era

Abstract: Pediatric brain tumors are a leading cause of cancer-related death in children. In recent years, the application of next-generation sequencing and other high-throughput technologies to analysis of pediatric brain tumors has generated an abundance of molecular information. This has provided an unprecedented understanding of their biology and is refining tumor classification into clinically relevant subgroups. In this review, we provide an overview of our evolving molecular knowledge of the commonest pediatric b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…Interestingly, one particular study has been demonstrated that CSF-derived ctDNA can better reflect sequence mutations in driving genes when compared to plasma ctDNA [9]. Two new ways have been utilized to detect genetic mutations: droplet-digital PCR (ddPCR) and NGS [10][11][12]. One study has performed ddPCR with targeted amplican sequencing to search for mutations in CSF ctDNA of primary and metastatic brain tumor patients [13].…”
Section: Ctdnamentioning
confidence: 99%
“…Interestingly, one particular study has been demonstrated that CSF-derived ctDNA can better reflect sequence mutations in driving genes when compared to plasma ctDNA [9]. Two new ways have been utilized to detect genetic mutations: droplet-digital PCR (ddPCR) and NGS [10][11][12]. One study has performed ddPCR with targeted amplican sequencing to search for mutations in CSF ctDNA of primary and metastatic brain tumor patients [13].…”
Section: Ctdnamentioning
confidence: 99%
“…nucleolin, nestin, Ki67 and laminin subunit A2 ) as well as all major key players of the phosphoinositide 3-kinase pathway (seemingly implicated in ependymoma), were definitely detected. Pediatric brain tumors are a leading cause of cancer-related death in children (1). The application of high-throughput technologies (e.g.…”
Section: Abstract Background/aim: Proteomics Based On Highresolutionmentioning
confidence: 99%
“…Subsequent studies have confirmed PPM1D mutation frequencies of up to 9%–25% in DIPG. [ 6 , 8 , 9 , 10 ] PPM1D mutation is also related to the chemotherapy resistance of myeloid cancer. [ 11 ] We found that during clinical treatment, patients with brainstem glioma with PPM1D mutation have a shorter median survival time than PPM1D wild type patients.…”
Section: Introductionmentioning
confidence: 99%